2019
DOI: 10.1002/fuce.201900039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clamping Pressure on Cold Start Behavior of Polymer Electrolyte Fuel Cells

Abstract: Understanding the cold start process of polymer electrolyte fuel cell (PEFC) is crucial to the development of an advanced PEFC of good cold start performance or to the design of advanced cold start strategies. In this study, a three‐dimensional cold start model has been adapted and further developed to numerically investigate the cold start behavior under the applied clamping pressure, which was not considered in previous cold start modeling and simulation work. The PEFC cold start performance is studied under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Energies 2020, 13,3529 3 of 16 conventional and hybrid MPL were investigated and the adequate assembly pressure was decided for the experiment. The low-temperature start ability of a PEMFC with the dual hybrid structure was compared with those of PEMFCs with the single hybrid MPL structure and a conventional MPL and GDL structure under the optimum assembly pressure.…”
Section: Structures Of Hybrid Mpl/gdl and Experimental Apparatusmentioning
confidence: 99%
“…Energies 2020, 13,3529 3 of 16 conventional and hybrid MPL were investigated and the adequate assembly pressure was decided for the experiment. The low-temperature start ability of a PEMFC with the dual hybrid structure was compared with those of PEMFCs with the single hybrid MPL structure and a conventional MPL and GDL structure under the optimum assembly pressure.…”
Section: Structures Of Hybrid Mpl/gdl and Experimental Apparatusmentioning
confidence: 99%
“…The water movement in the cathode is related to the gap between the cathode CL and MPL, which is substantially impacted by the pressure with which the fuel cell is assembled. Dafalla [10] studied the influence of assembly pressure on characteristics such as the current distribution and fuel cell cold-start performance by establishing a three-dimensional mathematical model. The results demonstrated that increasing the clamping pressure during assembly not only increased ice accumulation in the cathode CL but also caused the membrane to dehydrate and decreased the cold-start performance.…”
Section: Introductionmentioning
confidence: 99%
“…The performance and reliability of PEMFC are not only dependent on materials and structure designs utilized, but also decided by the assembly conditions. Insufficient assembly pressure would cause higher interfacial contact resistance (ICR) and thermal contact resistance (TCR), whereas excessive assembly pressure may lead to mass transfer problems, or even the damage and failure of fuel cell components [4,5]. The ICR between GDL and BPP is one of the main reasons for ohmic losses and fuel cell performance reduction.…”
mentioning
confidence: 99%